1990
DOI: 10.1159/000235195
|View full text |Cite
|
Sign up to set email alerts
|

Allergens of Horse Epithelium

Abstract: We investigated five horse epithelial allergen extracts prepared from different qualities of raw material by several biochemical and immunochemical methods. Horse serum albumin and horse serum were used to identify serum-related antigens. We found high similarities as well as marked differences between the extracts. There were strong differences in the protein contents, the protein patterns obtained by isoelectric focusing and sodium dodecyl sulfate polyacrylamide gel electrophoresis, the total allergenic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…(10), Wahn etal. (24), and Franke et al (5) all found horse serum albumin to be of minor allergenic importance. Squire (21) and Ponterius etal.…”
Section: Sds-pa Ge I Immunoblottingmentioning
confidence: 97%
See 1 more Smart Citation
“…(10), Wahn etal. (24), and Franke et al (5) all found horse serum albumin to be of minor allergenic importance. Squire (21) and Ponterius etal.…”
Section: Sds-pa Ge I Immunoblottingmentioning
confidence: 97%
“…Lewenstein et al (10,11) and Markussen et al (12) isolated and partially characterized four allergens from horse hair and dandruff. Recently, Franke et al compared five different horse epithelial allergen extracts by biochemical and immunochemical methods, finding similarities, but also marked differetices, among the extracts (5). The present study was undertaken to compare the protein/glycoprotein content in extracts of horse dander and of horse hair and skin scrapings, to evaluate their ability to act as antigens and allergens by SDS-PAGE and isoelectric focusing (IEF) combined with immunoblotting and CIE/CRIE, and to identify possible allergens in horse dander and in hair and skin scraping extracts which may be of importance for diagnosis of horse allergy.…”
mentioning
confidence: 99%
“…3A). According to the Von Heijne weight matrix method (36), a favored putative signal peptidase cleavage site can be assigned between the Ala 15 and Gln 16 residues, generating a protein beginning with QQEENSDVAI. In contrast, the N-terminal end of the protein initially purified from hair dandruff (SDVAI) would result from a cleavage between Asn 20 and Ser 21 , which is not predicted by Von Heijne's rules.…”
Section: Molecularmentioning
confidence: 99%
“…In contrast, the N-terminal end of the protein initially purified from hair dandruff (SDVAI) would result from a cleavage between Asn 20 and Ser 21 , which is not predicted by Von Heijne's rules. Equ c1 was purified from saliva, and the microsequencing of its N-terminal peptide revealed a mixture of three sequences, one of them beginning at the predicted Gln 16 , but the others at Glu 18 and Ser 21 , respectively (Fig. 3B).…”
Section: Molecularmentioning
confidence: 99%
See 1 more Smart Citation